APPLICATION OF INTEGRAL CALCULUS IN ARCHITECTURE AND CONSTRUCTION. - Ne’matov Asliddin Rabbimqulovich (International Engineering Journal For Research & Development, 2020)
This work reflects the application of integral calculus to architecture and construction. The purpose of this paper is to explore the possibility of using integrals to solve architectural problems.